Ecology of algal blooms in the Bay of Quinte: composition, diversity and dynamics. Issue 4 (2nd October 2018) - Munawar, M.; Fitzpatrick, M.; Niblock, H.; Rozon, R.; Lorimer, J.; Kling, H.
Abstract : A total of 25 algal blooms were observed during three separate surveys of the Bay of Quinte, Lake Ontario, conducted during August 2010, September 2010 and September 2011. Here we define algal blooms based on the direct measurement of phytoplankton biomass (>3 g m −3 ) and not proxy measures such as chlorophyll a . In this chronically eutrophic embayment, we observed 8 diatom blooms ( Aulacoseira spp.), 7 cyanobacteria blooms (Dolichospermum, Gloeotrichia, Microcystis, etc.) and 10 more that were mixtures of both taxa. At the cyano-bloom sites, ≈50% or more of the total biomass was composed of species known to be toxigenic. High rates of primary production (40 – 160 mg C m −3 h −1 ) by the larger algal size classes (>20 μm and 2–20 μm) indicated that there were few constraints on photosynthesis during bloom events (both diatom and cyanobacteria). Productivity to biomass quotients were considerably higher for filamentous algal forms (>9 for both diatoms and cyanobacteria) compared to colonial cyanobacteria (<5) suggesting that filamentous algae are more photosynthetically efficient. Our findings showed the observed algal blooms to be diverse and dynamic entities; management strategies need to recognize the unique characteristics of individual bloom events. Moreover, long term research and monitoring programs are necessary for the application of adaptive management strategies in order to address persistent ecosystem stressors like eutrophication.